Political storm after municipal elections in Bosnia and Herzegovina in 1928 - Užičanin, Salkan (Historical Thought, 2025)
Based on available sources and literature, this paper analyzes the first municipal elections in Bosnia and Herzegovina within the Kingdom of Serbs, Croats and Slovenes, their results and the consequences caused by the establishment of local authorities on the state-level political scene. Although the elections were held in the shadow of the great political crisis that shook the Kingdom of Serbs, Croats and Slovenes from the assassination in the Assembly on June 20, 1928, a sharp election campaign, led in a nationalist tone, in shady political circumstances and with pronounced national tensions, provoked new social and national divisions. Inter-party skirmishes and mutual accusations shook an earlier coalition agreement between the Yugoslav Muslim Organization and the People’s Radical Party, which required parties to collaborate wherever possible after the election and work to restore trust among the people, which was severely disrupted by years of nationalist and chauvinist harangue. Special difficulties arose after the election and constitution of municipal councils, when parties in some places formed a coalition with other political parties. The constitution of municipal leaderships in some places without the NRS the Bosnian Radicals characterized as a pact against the Serbs and launched an action to oust the JMO from the government. Thus, the local elections in Bosnia and Herzegovina heated up already the tense political atmosphere and became a first-class issue in the country.